Comparison of three-point belt fit between humans and ATDs in rear seats. (28th February 2018) - Park, Jangwoon; Ebert, Sheila M.; Reed, Matthew P.; Hallman, Jason J.
ABSTRACT: Objective : The anthropomorphic test devices (ATDs) in the Hybrid III family are widely used as human surrogates to test the crash performance of vehicles. A previous study demonstrated that passenger belt fit in rear seats was affected by high body mass index (BMI) and to a lesser extent by increased age. Specifically, the lap belt was worn higher and more forward as BMI and age increased. The objective of this study was to compare passenger belt fit to the belt fit achieved when installing the small female and midsize male Hybrid III adult ATDs using standard procedures. Methods : The ATDs were installed using standardized procedures in the same conditions previously used with volunteers. Belt fit was measured using methods analogous to those used for the volunteers. Comparative human belt fit values were obtained by using regression analysis with the volunteer data to calculate the mean expected belt fit for people the same size as the ATDs. Results : For the small female ATD, the upper edge of the lap belt was on average 59 mm forward and 11 mm above the anterior–superior iliac spine (ASIS) landmark on the ATD pelvis bone. In contrast, the belt position for similar size passengers was 17 mm forward and 22 mm above the ASIS. For the midsize male ATD, the belt was 34 mm forward and 10 mm above the ASIS. For similar size passengers, the position was 38 mm forward and 44 mm above the ASIS. For context, the belt width in this study was 38 mm. Discussion : The results suggest that the lap belt fit obtained by ATDs is more idealized but more repeatable compared to that achieved by similar size passengers. Future standardization efforts should consider investigating whether new belt-positioning procedures with ATDs may improve the biofidelity of ATD response.